Speed control strategy for tractor assisted driving based on chassis dynamometer test - Zhang, Xiaorui; Zhou, Zhili (International Journal of Agricultural and Biological Engineering, 2021)
Realizing automation of the chassis dynamometer and the unmanned test workshop is an inevitable trend in the development of new tractor products. The accuracy of the speed control of the test tractor directly affects the accuracy of the test loading force. In order to meet the purpose of precise control of the test tractor speed on the chassis dynamometer, a fuzzy PID control strategy was developed according to the working principle of assisted driving. On the basis of traditional PID control, the parameters of fuzzy inference module were added for real-time adjustment to achieve faster response to tractor speed changes and more precise control of tractor speed. The Matlab-Cruise co-simulation platform was established for simulation, and the experiment was verified by the tractor chassis dynamometer using the NEDC working condition and tractor ploughing working condition. The results show that both PID control and fuzzy PID control can achieve tractor speed following accuracy of ±0.5 km/h. Fuzzy PID control has higher tractor speed following accuracy, faster response when speed changes, less tractor speed fluctuation, and overall control effect is better than PID control. The research results can provide a reference for the realization of the chassis dynamometer unmanned test workshop.Keywords: tractor, chassis dynamometer, assisted driving, speed control, fuzzy PIDDOI: 10.25165/j.ijabe.20211406.6380Citation: Zhang X R, Zhou Z L. Speed control strategy for tractor assisted driving based on chassis dynamometer test. Int J Agric & Biol Eng, 2021; 14(6): 169–175.